The Strategy of Potential Cevelopment of Cacaban Kidul Village, Purworejo Regency, Central Java Province as a Tourism Village - Iqlima Ramadhani; Hendraningrum, Rr Adi; Rachim, Amanda Rizka; Isfina Rusvitasari; Nurizki, Reza (Politeknik Negeri Bandung, 2023)
Cacaban Kidul Village has various potentials that can be developed as a tourism village. Among them are natural tourism and community based tourism. However, in developing the potential of Cacaban Kidul Village there are still several internal and external factors faced by Cacaban Kidul Village, which influence the development of the village's tourism potential. This study aims to analyze tourism potential, identify internal and external factors that influence the development of tourism potential, and provide alternative strategies in developing tourism potential in Cacaban Kidul Village. This research is a research that uses qualitative methods with a descriptive approach. The data analysis used is SWOT analysis to determine and provide an overview of strategies that can be carried out for the development of tourism potential in Cacaban Kidul Village, Purworejo Regency, Central Java.